ANALISIS KINERJA KEUANGAN PT. BANK ACEH SYARIAH DENGAN MENGGUNAKAN MODEL SHARIA CONFORMITY AND PROFITABILITY (SCnP) DAN CAMEL - Sri Jayusma; Musfiari Haridhi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The purpose of this study was to analyze the financial performance of PT. Bank Aceh Syariah by using Sharia Conformity and Profitability ( SCnP ) and CAMEL models, and to see the difference in the level of financial performance of the both models. Type of this research is quantitative descriptive analysis. The object of this research is PT. Bank Aceh Syariah . The data used are monthly financial statement for 28 months obtained from the official website of the bank. The results of this study show that by using SCnP the performance of banks is spread into four different quadrant almost every month and in 2018 the bank was able to show an increase which is on average Upper Right Quadrant (URQ). As for using CAMEL model, it shows good performance at the ratio of CAR, RORA, BOPO and FDR. While at the ratio of NPM and ROA the bank has not been able to reach the established criteria.